Futile Recanalization after Endovascular Therapy in Acute Ischemic Stroke. (9th May 2018) - Nie, Ximing; Pu, Yuehua; Zhang, Zhe; Liu, Xin; Duan, Wanying; Liu, Liping
Abstract : Early recanalization after endovascular treatment could improve the prognosis of acute ischemia stroke. Futile recanalization often occurred which was one of the main causes of failure. By now the mechanisms of futile recanalization were not clear. They are probably concerned with bad collateral circulation, subacute reocclusion, large hypoperfusion volumes, microvascular compromise, and impaired cerebral autoregulation. Previous research found that some of the image markers could be used as the accurate predictors for poor prognosis after successful treatment in order to identify the patients who were not suitable for recanalization and reduce some of the unnecessary cost. Predictors for futile recanalization mentioned in our article can be used for supplement to make decision for endovascular treatment.